Application of Morphometric Analysis to Identify Alewife Stock Structure in the Gulf of Maine. Issue 1 (22nd January 2013) - Lee Cronin‐Fine,; Stockwell, Jason D.; Whitener, Zachary T.; Labbe, Ellen M.; Willis, Theodore V.; Wilson, Karen A.
Abstract: Alewife Alosa pseudoharengus is an anadromous clupeid fish of long‐standing ecological and socioeconomic importance along the Atlantic coast of North America. Since the 1970s, Alewife populations have been declining throughout the species' range. A number of hypotheses have been proposed to explain the decline, but a lack of basic information on population demographics inhibits hypothesis testing. In this study, we evaluated the use of morphometric analysis to discriminate among spawning stocks of Alewives collected from 24 sites in Maine and one site in Massachusetts. We first identified 10 morphometric measurements that were not influenced by the freezing–thawing process, and then used principal component and discriminant function analyses to develop stock‐structure classification models from these 10 measurements. Classification models were able to discriminate Alewives to be from Maine or the single Massachusetts site 100% of the time. In addition, classification models correctly classified pooled sampling sites from the extreme western and eastern parts of Maine with 64% accuracy. Morphometric analysis may therefore provide an easily accessible, comparatively fast, and inexpensive method to discriminate marine‐captured Alewives spawned in areas separated by major biogeographic regions, large geographic distances (100s of kilometers), or both, and thus help inform questions about stock composition at these spatial scales for assessment surveys and bycatch events. Received March 30, 2012; accepted October 14, 2012.